2022
DOI: 10.3390/nu14214673
|View full text |Cite
|
Sign up to set email alerts
|

Once-Weekly Subcutaneous Semaglutide Improves Fatty Liver Disease in Patients with Type 2 Diabetes: A 52-Week Prospective Real-Life Study

Abstract: Background. Nonalcoholic fatty liver disease (NAFLD) is commonly observed in patients with type 2 diabetes (T2D). Semaglutide, a glucagon-like peptide 1 receptor agonist, may have a therapeutic role by targeting common mechanisms involved in the pathophysiology of T2D and NAFLD. The study aimed to assess the effectiveness of Semaglutide on NAFLD in patients with T2D. Methods. Forty-eight patients were treated with subcutaneous Semaglutide in add-on to metformin for 52 weeks. After the baseline visit (T0), foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…[24][25][26][27][28] Both dulaglutide and semaglutide have been reported to improve fatty liver. 29,30 To the best of our knowledge, there are no prospective comparative reports on the effects of dulaglutide and semaglutide on liver fat percentage at doses approved in Japan. This study revealed that only semaglutide significantly increased the L/S ratio during the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28] Both dulaglutide and semaglutide have been reported to improve fatty liver. 29,30 To the best of our knowledge, there are no prospective comparative reports on the effects of dulaglutide and semaglutide on liver fat percentage at doses approved in Japan. This study revealed that only semaglutide significantly increased the L/S ratio during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…GLP‐1RA has been reported to have positive effect on NAFLD similar to pioglitazone and sodium‐glucose cotransporter 2 inhibitors 24–28 . Both dulaglutide and semaglutide have been reported to improve fatty liver 29,30 . To the best of our knowledge, there are no prospective comparative reports on the effects of dulaglutide and semaglutide on liver fat percentage at doses approved in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…[265][266][267] Furthermore, they have a positive impact on body composition through significant improvements in VAT, fat mass index (FMI), epicardial fat and hepatic steatosis, thus making them an appealing drug in the management of different obesity phenotypes. [268][269][270] FGF21 is also being proposed as a potential novel therapeutic modality, especially with regard to improving hepatic steatosis. 271,272 Bariatric surgery to date is still the most effective strategy for weight loss and weight loss maintenance.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Furthermore, studies have shown that GLP‐1 analogues also exert positive effects on the cardiovascular system through weight‐independent mechanisms, including improved vascular endothelial function, ischaemic conditioning and reduction in systemic inflammation 265–267 . Furthermore, they have a positive impact on body composition through significant improvements in VAT, fat mass index (FMI), epicardial fat and hepatic steatosis, thus making them an appealing drug in the management of different obesity phenotypes 268–270 . FGF21 is also being proposed as a potential novel therapeutic modality, especially with regard to improving hepatic steatosis 271,272 …”
Section: Natural Course and Clinical Implications Of Mho And Muhnwmentioning
confidence: 99%
“…Besides, bariatric surgeries significantly reduced cardiovascular events and prolonged the overall survival of patients [11]. Newly, the development of semaglutide, a glucagon-like peptide-1 (GLP1) agonist, and tirzepatide, a dual agonist of GLP1 and glucose-dependent insulinotropic polypeptide, also known as gastric inhibitory polypeptide (GIP), revolutionized the treatment of obesity, with simultaneous protective effects on atherosclerotic cardiovascular disease and NAFLD [12,13,[17][18][19]. Interestingly, the newly published study by Jastreboff et al indicated that retatrutide, a triple agonist of GIP, GLP1, and glucagon receptor, led to greater achievement in the management of obesity with up to -24.2 % percentage change in body weight after 48 weeks of treatment [20].…”
Section: Introductionmentioning
confidence: 99%